Effect of mobile phone-based health insurance contribution payment system on retention of coverage in the National Health Insurance Scheme in Ghana: an evaluation study - Eric Nsiah-Boateng; Mariam Musah; Collins Danso Akuamoah; Francis Asenso-Boadi; Francis-Xavier; Bernard Okoe Boye (BMC, 2023)
Abstract Background Ghana introduced a mobile phone-based contribution payment system in its national health insurance scheme (NHIS) in December 2018 to improve the process of enrolment. We evaluated the effect of this digital health intervention on retention of coverage in the Scheme, one year after its implementation. Methods We used NHIS enrolment data for the period, 1 December 2018-31 December 2019. Descriptive statistics and propensity-score matching method were performed to examine a sample of 57,993 members' data. Results Proportion of members who renewed their membership in the NHIS via the mobile phone-based contribution payment system increased from 0% to 8.5% whilst those who did so through the office-based system only grew from 4.7% to 6.4% over the study period. The chance of renewing membership was higher by 17.4 percentage points for users of the mobile phone-based contribution payment system, compared to those who used the office-based contribution payment system. The effect was greater for the informal sector workers, males and the unmarried. Conclusions The mobile phone-based health insurance renewal system is improving coverage in the NHIS particularly for members who hitherto were less likely to renew their membership. Policy makers need to devise an innovative way for new members and all member categories to enrol using this payment system to accelerate progress towards attainment of universal health coverage. Further study needs to be conducted using mixed-method design with inclusion of more variables.